2019
DOI: 10.1016/j.gie.2018.09.028
|View full text |Cite
|
Sign up to set email alerts
|

G-EYE colonoscopy is superior to standard colonoscopy for increasing adenoma detection rate: an international randomized controlled trial (with videos)

Abstract: Background and Aims: Colorectal cancer (CRC) is largely preventable with routine screening and surveillance colonoscopy; however, interval cancers arising from precancerous lesions missed by standard colonoscopy still occur. An increased adenoma detection rate (ADR) has been found to be inversely associated with interval cancers. The G-EYE device includes a reusable balloon integrated at the distal tip of a standard colonoscope, which flattens haustral folds, centralizes the colonoscope's optics, and reduces b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 45 publications
1
33
0
1
Order By: Relevance
“…19 A colonoscope with a large balloon at the bending section which slows withdrawal and compresses folds (G-EYE colonoscope; Smart Medical Systems Ltd., Ra'anana, Israel) also improved serrated lesion detection rates in a large randomized controlled study (2.7% vs 0.8%, p=0.036). 20 A study that looked at narrow-band imaging (NBI; Olympus, Tokyo, Japan) for serrated polyp detection suggested a statistical trend toward improved detection with a mean number of serrated lesions proximal to the sigmoid of 0.51 with NBI versus 0.39 for white light (p=0.085). 21 A subsequent metaanalysis of NBI for detection of non-adenomatous (serrated) lesions suggested significantly improved detection with either first or second generation "Bright" NBI.…”
Section: Sessile Serrated Polyps and Their Endoscopic Detectionmentioning
confidence: 99%
“…19 A colonoscope with a large balloon at the bending section which slows withdrawal and compresses folds (G-EYE colonoscope; Smart Medical Systems Ltd., Ra'anana, Israel) also improved serrated lesion detection rates in a large randomized controlled study (2.7% vs 0.8%, p=0.036). 20 A study that looked at narrow-band imaging (NBI; Olympus, Tokyo, Japan) for serrated polyp detection suggested a statistical trend toward improved detection with a mean number of serrated lesions proximal to the sigmoid of 0.51 with NBI versus 0.39 for white light (p=0.085). 21 A subsequent metaanalysis of NBI for detection of non-adenomatous (serrated) lesions suggested significantly improved detection with either first or second generation "Bright" NBI.…”
Section: Sessile Serrated Polyps and Their Endoscopic Detectionmentioning
confidence: 99%
“…WT was significantly different in four studies; in three studies, WT was longer in the BFT group [21,24,27], and in 1 study, WT was longer in the CC group [28]. Mean WT was 7.8 versus 7.7 min for BFT and CC, respectively (P G 0.05, mean difference 0.08 min).…”
Section: Withdrawal Timementioning
confidence: 88%
“…The G-Eye endoscope (NaviAid G-EYE, SMART Medical Systems Ltd., Ra’anana, Israel) has an integrated (moderately inflated) balloon serving as its bending part, which allows both the withdrawal and instrument stabilization together with flattening the haustral folds and inhibiting the slippage of the bowel ( Figure 2 D). A recent study by Shirin et al [ 57 ] found that the technique yielded a higher detection rate of adenomas/polyps (ADR and PDR), including well-formed, flat and sessile serrated ones, when compared to SC. When meta-analysed with a previously published paper by Halpern et al [ 58 ], Keulen et al [ 59 ] discovered that ADR by means of the G-Eye endoscope is 30% higher than SC.…”
Section: Non-robotic Colonoscopes and Colonoscopy Adjuncts In The mentioning
confidence: 99%